2009
DOI: 10.1089/dia.2008.0094
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Isometric Handgrip Test to Show Autonomic Damage in People with Diabetes

Abstract: Diabetes is associated with a reduction in handgrip strength and significantly impaired autonomic function during and after isometric exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…81 Handgrip strength has been shown to be an indicator of autonomic damage in individuals with diabetes. 82 …”
Section: Discussionmentioning
confidence: 99%
“…81 Handgrip strength has been shown to be an indicator of autonomic damage in individuals with diabetes. 82 …”
Section: Discussionmentioning
confidence: 99%
“…The reported study interventions consisted of cognitive exercises (k = 21) (Cacioppo et al, 2000;Steptoe et al, 2002Wood et al, 2002;Kunz-Ebrecht et al, 2003;Marmot, 2005, 2006;Hamer and Steptoe, 2007;Capuana et al, 2012;Christensen Stephanie and Wright Heather, 2014;Collste et al, 2014;Lin et al, 2014Lin et al, , 2017aCrowley Olga et al, 2016;Norcliffe-Kaufmann et al, 2016;Wawrzyniak Andrew et al, 2016;Beer Noa et al, 2017;Betz Linda et al, 2017;Kuraoka et al, 2019;Perpetuini et al, 2019), cardiorespiratory exercises (k = 18) (Perini et al, 2000;Bartels Matthew et al, 2003;Takahashi et al, 2003;Davrath Linda et al, 2006;Virtanen et al, 2007;Mayumi et al, 2008;Karavirta et al, 2009;Dourado et al, 2010;Alves Naiane Ferraz et al, 2011;Sales et al, 2011;Wang Norman et al, 2011;Corrêa et al, 2013;Ahmadian and Dabidi Roshan, 2015;Junior Adalberto et al, 2019;Rodrigues Jhennyfer et al, 2019;Wittstein et al, 2019;Kaltsatou et al, 2020), resistance exercises (k = 6) (Piepoli et al, 1996;Petrofsky et al, 2009;Millar et al, 2011;<...>…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Bartels Matthew et al, 2003;Alves Naiane Ferraz et al, 2011;Kaltsatou et al, 2020 Alves Naiane Ferraz et al, 2011;Ahmadian and Dabidi Roshan, 2015;Rodrigues Jhennyfer et al, 2019;Kaltsatou et al, 2020 Takahashi et al, 2003;Davrath Linda et al, 2006;Virtanen et al, 2007;Mayumi et al, 2008;Karavirta et al, 2009;Wang Norman et al, 2011;Corrêa et al, 2013;Ahmadian and Dabidi Roshan, 2015;Beer et al, 2017 (Continued) Frontiers in Physiology | www.frontiersin.org Piepoli et al, 1996;Petrofsky et al, 2009;Millar et al, 2011;Beer Noa et al, 2017 ց 1 Beer Noa et al, 2017 Millar et al, 2011;Machado-Vidotti et al, 2014;Beer Noa et al, 2017 ↑ n = significant (p < 0.05) increase from resting HRV, ր n = increasing trend (not significant or not statistically tested) → n = no significant change from resting HRV, ց n = decreasing trend (not significant or not statistically tested), ↓ n = significant (p < 0.05) decrease from resting HRV, n = number of studies reporting this effect, NR = not reported.…”
Section: Phasic Hrv Responses To Cognitive Exercisesmentioning
confidence: 99%
“…Interestingly, a recent cross‐sectional study has shown that reduced heart rate variability is associated with both early and late measures of DPN, particularly sural sensory nerve dysfunction . In addition, diabetes, and to a lesser extent age‐induced reduction in handgrip strength was associated with significantly impaired autonomic function and forearm and skin blood flow during and after isometric exercise . The autonomic nervous system, together with the intrinsic vascular smooth muscle cell myogenic response and endothelial cell autoregulation, plays a major role in capillary recruitment, a central mechanism favouring muscle metabolism during contraction.…”
Section: Mechanisms Responsible For the Decline In Neuromuscular Funcmentioning
confidence: 99%